Comparative analysis between brazilian and canadian eletronic democratization: the Dialoga Brazil and Suggest a Dataset - Bizelli, Thais Vargas [UNESP]; Bizelli, Jose Luis [UNESP]; Santos Cruz, Jose Anderson [UNESP] (Editora Univ Leopoldlanum, 2021)
This article aims to promote a discussion on a comparison between two electronic governance instruments, consubstantiated in two digital platforms: Dialoga Brasil and Suggest a Dataset - Canadian site, where citizens can demand specific information. To do so, it performs an initial conceptualization of the terms used throughout the research, as well as it presents a detailed analysis of both Internet portals. A history of the Internet use in both countries is also demonstrated considering both the access and the use of ICT by the respective governments. We intend to demonstrate how national politics (the paths chosen by the governing authorities, as well as the solidity of institutions and democratic regimes) influences the process of consolidating e-democracy.
Keywords: Eletronic governance; e-democracy; Dialoga Brasil; Suggest a Dataset